2019
DOI: 10.16965/ijar.2019.122
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Analysis of Lumbar Vertebrae and Its Applied Clinical Importance

Abstract: The lumbosacral spine is the region of transition from the appendicular to the axial skeleton. Accidents, degenerative conditions, congenital defects and neoplastic metastases often affect the lumbar region. Low back pain resulting from lumbar canal stenosis is one of the major complaints in young to adult population. Apart from that lumbar vertebrae morphometry is required in many surgical as well as anaesthetic procedures.Aims and objectives: The present study was undertaken to determine the morphometry of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…It again showed increase from L4-L5. 26 It was also observed that the mean values for anteroposterior diameter of vertebral canal were found to be higher in males than females at L2 and L4 vertebral levels whereas these values were found to be higher among females at L1, L3 and L5 vertebral levels. Contrary to this study, Zhou et al and Alam et al, suggested that the antero-posterior diameter was higher among males than females at all levels of vertebrae.…”
Section: Discussionmentioning
confidence: 83%
“…It again showed increase from L4-L5. 26 It was also observed that the mean values for anteroposterior diameter of vertebral canal were found to be higher in males than females at L2 and L4 vertebral levels whereas these values were found to be higher among females at L1, L3 and L5 vertebral levels. Contrary to this study, Zhou et al and Alam et al, suggested that the antero-posterior diameter was higher among males than females at all levels of vertebrae.…”
Section: Discussionmentioning
confidence: 83%
“…17,23,24 Al-Rakhawy et al and Banik et al encountered a dip in IPD at L3 level while Attar et al found the mean IPD increase to halt at L2 level. 23,25,26 Some studies have reported much larger values of IPD at L5 level. 5,24,25 The remarkably higher value at L5 was probably caused by the different configuration of the vertebra, in which the pedicles were more lateroventrally implanted on the body and were fused with the transverse processes.…”
Section: Discussionmentioning
confidence: 99%
“…23,25,26 Some studies have reported much larger values of IPD at L5 level. 5,24,25 The remarkably higher value at L5 was probably caused by the different configuration of the vertebra, in which the pedicles were more lateroventrally implanted on the body and were fused with the transverse processes. 27 Mansur et al noted that the transverse diameter of the spinal canal of any lumbar vertebra is proportional to the size of the vertebral body at that level and that its ratio with the body would be more helpful for identifyng spinal canal stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…al. (10), it was found that all the vertebral diameters increase from L1 to L5 except at the L3 level, where a decrease in diameter was noted. Similar results were noted in studies by El Rakhawy et al (11) and Kapoor et al (12).…”
Section: Review Of Literature Review Of Literaturementioning
confidence: 89%